Profile of Infrastructure and Pedagogic Competencies of Teachers in SMP and SMA/SMK in Waisai District, Raja Ampat Regency, West Papua Province - Watem, Maikel; Nunaki, Jan Hendrik; Wambrauw, Hengky L (Inornatus: Biology Education Journal, 2018)
This study aims to find out an overview of Infrastructure Facilities and Pedagogic Competencies of Teachers in SMP and SMA/MK in Waisai District, Raja Ampat Regency, West Papua Province. This research was a descriptive study, data collection using questionnaires, namely infrastructure principal questionnaire for school principals and teacher pedagogic competency questionnaire divided by each teacher in the education unit conducted by the study. The results of the analysis in this study infrastructure in 3 junior high schools the average percentage shows that SMP Negeri 14 has a very high percentage of up to 98%, in SMP Negeri 21 reaches 55%, and SMP YPK Alfa Omega 67% so that both schools are still in low category. In the high school / vocational school, the results showed that the State High School 1 and SMK 2 were in the very high percentage category, namely SMA Negeri 1 reached 97%, and SMK Negeri 2 reached 92%, while SMA Negeri 14 reached 66%, so it was still in the low category. While the pedagogic competence of teachers in the 3 SMP results showed that each school had not achieved a significant percentage value, namely in SMP Negeri 14 reached 7,352%, SMP Negeri 21 reached 5,617%, and YPK Alfa Omega SMP reached 8,333%. in high school and vocational high school results also show that each school has not achieved a significant percentage value, namely at State 1 High School reached 6.410%, State High School 14 reached 8.196%, and State Vocational High School 2 reached 5.813%